Multistakeholder Collaboration to Enhance the Scalability of Jarwo Super Technology: An Innovation Platform Perspective - Winda Anestya Ayunda; Indah Purwaningsih; Lutfah Ariana; Cecep Ibrahim (National Research and Innovation Agency, Indonesia, 2022)
The process of accelerating the diffusion of research and development (R&D) results in an agricultural innovation system (AIS) can be realized through an innovation platform approach. This study examines the collaboration of multi-stakeholders in the process of development and diffusion of the Jajar Legowo (Jarwo) Super technology through the perspective of innovation platform. There have been few studies in the area to look at the structure of technology diffusion process to achieve a scalability of impact. This study will fill the gap by looking at the structure of multi-stakeholders’ network and the working mechanism of the platform to get understanding on the delivery process of Public Research Organization (PRO)’s research result at a systemic level. The analysis of this research is equipped with the application of a co-word analysis. This tool is used to map issues based on the actor's function, namely the role in the development and diffusion of Jarwo Super technology. The results of the study will contribute to the theoretical development of innovation platform in AIS. It also provides a basis for policy makers and related stakeholders on how innovation platform can strengthen agricultural development programs in a wider organizational context.